Management of immune checkpoint inhibitor in patients with cancer and pre-existing inflammatory bowel disease: Recommendations from the GETAID. Issue 9 (September 2022) - Amiot, Aurelien; Laharie, David; Malamut, Georgia; Serrero, Melanie; Poullenot, Florian; ,; Peyrin-Biroulet, Laurent; Laharie, David; Bourreille, Arnaud; Vuitton, Lucine; Bouguen, Guillaume; Abitbol, Vered; et al.
Summary: Background and aims: There is no consensus on the management of immune checkpoint inhibitor (ICI) for treating cancer in patients with pre-existing inflammatory bowel disease (IBD). The Groupe d'Étude Thérapeutique des Affections Inflammatoires du tube Digestif (GETAID) aimed to provide recommendations on this topic. Methods: A dedicated working group performed a comprehensive expert-based review of the literature, generated clinical key question and shaped recommendations that were further voted for approval by the educational and scientific committees of the GETAID. Using consensus methods, treatment modalities were defined by vote. Results: Majority of patients with IBD in clinical remission can be treated with ICI after cancer diagnosis. The rate of relapse or immune-related diarrhoea or colitis upon ICI treatment is up to 39.8% and is maximal with ICI combination therapy compared to monotherapies. When starting ICI in a patient with IBD, it is recommended to assess disease activity and pursue ongoing maintenance therapy. In case of relapse or immune-related diarrhoea or colitis upon ICI treatment, treatment depends on grading of diarrhoea or colitis and may include corticosteroid therapy, infliximab and/or vedolizumab. Conclusions: In the present publication, we provided recommendations, which may assist gastroenterologists, haematologists, and oncologists for a better management of patients with pre-existing IBD before and during cancer treatment with ICI.